Dekadensi Moral Elit Politik Sebagai Ancaman Kesejahteraan Masyarakat - Rofidah, Lailatur (Journal of Integrative International Relations, 2017)
Moral decadence of the political elites led to the emegence cases that have direct impact to the community. The practice of â€œMoney Politicsâ€ as concrete manifesatation of moral decadence of the political elites in campaign periode led to the biggest case that is corruption. Corruption is not only detrimental to the state but also led to the suspension of infrastructure development, so that the public welfare was inhibited. If moral decadence of the political elites increases, then the public welfare decrases continuously. To handle the moral decadence we can do some ways, involving moral or character education; establishing knowledge and implementation of Pancasila values; and tighten the law on corruptors.